A project of aesthetic renovation in the Argentine and Latin American musical fields during the sixties: the Latin American Center of Higher Musical Studies (CLAEM). Advances of a research in progress. (Revista Argentina de Musicología, 2007)
The present work is a preliminary text of an ongoing research project based on the hypothesis of the decisive importance of CLAEM in the Latin American musical field concerning technical and esthetic renovation related to the post war international avant-garde music. lts purpose is to underline to what extent the center's activity constituted a fundamental contribution to that renovation. Convergent factors that made the creation and activity of CLAEM possible are indicated. The transnational modernization impulse. expressed on the local level by the development policy, on one hand. and the U.S.A. strategy through the Alliance for Progress. on the other hand. a key factor in the creation and functioning of CLAEM. To back up the hypothesis proposed. materials from different sources -programme notes, lectures, correspondence, criticism. and news- in various journals are provided.
Keywords: Latin American musical avant-garde; Di Tella Institute; Ginastera; modernization; technical and aesthelic renovation